Master techniques in Ophthalmic surgery - Roy, Frederick Hampton; Tindall, Renee (Jaypee Brothers Medical Publishers, 2015)
Master Techniques in Ophthalmic Surgery covers all topics related to ophthalmic surgery in 149 chapters. This book provides diagnoses and indications for surgery, surgical techniques, outcomes and references for a variety of ophthalmic conditions. Enhanced by 1116 full colour images.